Role of Luminex Crossmatch in Renal Transplantation – A Comprehensive Case Study - Rajeshwari Basavanna; Suchita P. Jogale; Anand S. Deshpande (Indian Journal of Transplantation)
The significance of pre-transplant screening for donor-specific anti-HLA antibodies dates back to the 1960s. The advent of Complement Dependent Cytotoxicity (CDC) assay, flow cytometry, and solid-phase assays has transformed the detection of anti-HLA antibodies, particularly in renal transplant cases. While the utilization of solid-phase assays offers numerous advantages, it is imperative to acknowledge their inherent limitations when striving to deliver accurate results to patients. In this study, we present three cases characterized by false positivity observed either in cross-matching or HLA antibody screening. These instances underscore the critical role of clinical history consideration and the adoption of highly sensitive and specific multiple platforms to effectively address and rectify false positive and false negative results. This approach enhances patient care and ensures the provision of accurate and reliable pre-transplant assessments and post-transplant monitoring.